An ancestral role for the mitochondrial pyruvate carrier in glucose-stimulated insulin secretion - Kyle S. McCommis; Wesley T. Hodges; Daniel K. Bricker; Dona R. Wisidagama; Vincent Compan; Maria S. Remedi; Carl S. Thummel; Brian N. Finck (Elsevier, 2016)
Objective: Transport of pyruvate into the mitochondrial matrix by the Mitochondrial Pyruvate Carrier (MPC) is an important and rate-limiting step in its metabolism. In pancreatic β-cells, mitochondrial pyruvate metabolism is thought to be important for glucose sensing and glucose-stimulated insulin secretion. Methods: To evaluate the role that the MPC plays in maintaining systemic glucose homeostasis, we used genetically-engineered Drosophila and mice with loss of MPC activity in insulin-producing cells. Results: In both species, MPC deficiency results in elevated blood sugar concentrations and glucose intolerance accompanied by impaired glucose-stimulated insulin secretion. In mouse islets, β-cell MPC-deficiency resulted in decreased respiration with glucose, ATP-sensitive potassium (KATP) channel hyperactivity, and impaired insulin release. Moreover, treatment of pancreas-specific MPC knockout mice with glibenclamide, a sulfonylurea KATP channel inhibitor, improved defects in islet insulin secretion and abnormalities in glucose homeostasis in vivo. Finally, using a recently-developed biosensor for MPC activity, we show that the MPC is rapidly stimulated by glucose treatment in INS-1 insulinoma cells suggesting that glucose sensing is coupled to mitochondrial pyruvate carrier activity. Conclusions: Altogether, these studies suggest that the MPC plays an important and ancestral role in insulin-secreting cells in mediating glucose sensing, regulating insulin secretion, and controlling systemic glycemia. Keywords: Stimulus-coupled secretion, Insulin, β-Cell, Diabetes, Pyruvate, Mitochondria, Drosophila